Polish Companies and ICT Infrastructure - A Regional Perspective - Kiercz, Oskar (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The growing disparity in development between Poland's regions has become a pressing problem for the country's economy today. Here disparity applies not only to the standard of living, but also to information and communication technologies (ICTs) used by both individual and larger business entities, and it indicates the division into well-developed and underdeveloped regions. This phenomenon is slowing down the country's socio-economic development. The article assesses the use of ICTs by Polish enterprises in 2010 relative to other EU member countries and regional structures based on statistical data provided by Eurostat and The Central Office of Statistics.